Acute liver failure in adults - Çalışkan, Ali Rıza; Harputluoğlu, Murat (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Çalışkan AR, Harputluoğlu M. Acute liver failure in adults. Turk J Gastroenterol 2019; 30(10): 938-9.